Penerapan Metode Muroja’ah Pada Mata Pelajaran Tahfidz Dalam Meningkatkan Kemampuan Menghafal Al-Qur'an Siswa - Sucia, Indriani; Aliyah, Adah; Rosadi, Adi (JURNAL MANAJEMEN PENDIDIKAN, 2025)
The Implementation Of The Muroja’ah Method In Tahfidz Subject To Improve Students' Ability To Memorize The Qur'anThis research is motivated by the low memorization ability of students in learning the Qur’an, as evidenced by 2025 data: only 20% of students achieved their memorization targets, 52% did not meet the target, and 40% experienced difficulties in memorizing. This problem is caused by weak repetition habits, the absence of a structured muroja’ah (review) schedule, and a lack of student learning motivation. One solution is to optimize the muroja’ah method as a strategy to strengthen and maintain Qur’anic memorization consistently. This study aims to explore the process of implementing the muroja’ah method, the forms of evaluation used, the obstacles encountered, and its impact on improving students’ memorization and learning motivation. The research uses a qualitative approach with a narrative method and a field research design. The subjects of this study include Qur’an teachers, the vice principal, subject teachers, and students. Data collection techniques include observation, interviews, and documentation. The data analysis involves data reduction, data presentation, and conclusion drawing. The research was conducted at SMP IT Al-Mamuriyyah, located in Cicurug, Sukabumi. The research findings are as follows: 1) The muroja’ah process is carried out through regular submission and scheduled repetition in class; 2) Memorization evaluation is conducted through direct monitoring and periodic memorization tests; 3) Challenges encountered include low motivation, lack of discipline, and limited time; 4) The impact of applying the muroja’ah method shows an improvement in memory retention, memorization quality, and students’ learning enthusiasm. This study concludes and proposes a model of steps to enhance Qur’an memorization through the optimization of the muroja’ah method, carried out routinely, measurably, and supported by the roles of teachers and parents. This model is accompanied by strategies to overcome students’ motivational and disciplinary challenges.